2023
DOI: 10.3390/bios13010136
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Gut-on-a-Chip: Fundamentals and Challenges

Abstract: The human gut is responsible for food digestion and absorption. Recently, growing evidence has shown its vital role in the proper functioning of other organs. Advances in microfluidic technologies have made a significant impact on the biomedical field. Specifically, organ-on-a-chip technology (OoC), which has become a popular substitute for animal models, is capable of imitating complex systems in vitro and has been used to study pathology and pharmacology. Over the past decade, reviews published focused more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 114 publications
0
13
0
Order By: Relevance
“…Moreover, this technology holds promise for advancing personalized medicine approaches, for example, by utilizing patient samples for testing medication responses. 8 Overall, the findings of Wang et al substantially contribute to unraveling the intricate links between dietary fiber intake, gut microbiota composition, microbial functional components, and circulating metabolites. This heightened understanding provides valuable insights into the complex mechanisms underlying the development of T2D.…”
Section: Article See P 842mentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, this technology holds promise for advancing personalized medicine approaches, for example, by utilizing patient samples for testing medication responses. 8 Overall, the findings of Wang et al substantially contribute to unraveling the intricate links between dietary fiber intake, gut microbiota composition, microbial functional components, and circulating metabolites. This heightened understanding provides valuable insights into the complex mechanisms underlying the development of T2D.…”
Section: Article See P 842mentioning
confidence: 95%
“…Moreover, this technology holds promise for advancing personalized medicine approaches, for example, by utilizing patient samples for testing medication responses. 8…”
mentioning
confidence: 99%
“…123 These systems can simulate in vivo fluidic flow, peristalsis-like motions, host-microbe crosstalk, and multi-cell type interactions, making them highly valuable for personalized medicine applications. Noteworthy contributions to this area of research can be found in the works of Xiang et al 124 and Thomas et al , 125 who have provided detailed discussions on gut-on-a-chip in vitro models. Additionally, several in vitro models have been specifically designed to replicate the presence of mucus in the gut, offering accurate and controlled testing environments for mucoadhesive devices.…”
Section: Current Challenges and Emerging Technologiesmentioning
confidence: 99%
“…As discussed in the previous text, the CTCs, ctDNA, and exosomes contain rich information about tumor characteristics. Nevertheless, these biomarkers are all released into large blood cell backgrounds from the primary tumor or metastatic deposits, causing their extremely low content in peripheral blood [19]. Moreover, many of these biomarkers have similar biophysical characteristics to normal blood components.…”
Section: Introductionmentioning
confidence: 99%
“…This approach provides a CTC detection specificity of >99% and sensitivity of >97%. As the detection of circulating cell-free nucleic acids depends on molecular biology techniques that are complex to operate and require additional analytical platforms (such as quantitative polymerase chain reaction [PCR], BEAMing, Safe-SeqS, and CAPP-Seq) [12][13][14][15][16][17][18][19][20][21][22], LB-based instruments are commonly used to extract cell-free nucleic acids. For example, the KingFisher Flex (Thermo Fisher Scientific, USA) instrument has been applied for cfDNA extraction from blood samples based on the magnetic enrichment technique [23], wherein cfDNA becomes positively charged by magnetic beads that bind to the negatively charged phosphate DNA backbone.…”
Section: Introductionmentioning
confidence: 99%